Developmental and epilepsy spectrum of KCNB1 encephalopathy with long‐term outcome. (21st September 2020) - Bar, Claire; Kuchenbuch, Mathieu; Barcia, Giulia; Schneider, Amy; Jennesson, Mélanie; Le Guyader, Gwenaël; Lesca, Gaetan; Mignot, Cyril; Montomoli, Martino; Parrini, Elena; Isnard, Hervé; Rolland, Anne; et al.
Abstract: Objective: We aimed to delineate the phenotypic spectrum and long‐term outcome of individuals with KCNB1 encephalopathy. Methods: We collected genetic, clinical, electroencephalographic, and imaging data of individuals with KCNB1 pathogenic variants recruited through an international collaboration, with the support of the family association "KCNB1 France." Patients were classified as having developmental and epileptic encephalopathy (DEE) or developmental encephalopathy (DE). In addition, we reviewed published cases and provided the long‐term outcome in patients older than 12 years from our series and from literature. Results: Our series included 36 patients (21 males, median age = 10 years, range = 1.6 months‐34 years). Twenty patients (56%) had DEE with infantile onset seizures (seizure onset = 10 months, range = 10 days‐3.5 years), whereas 16 (33%) had DE with late onset epilepsy in 10 (seizure onset = 5 years, range = 18 months‐25 years) and without epilepsy in six. Cognitive impairment was more severe in individuals with DEE compared to those with DE. Analysis of 73 individuals with KCNB1 pathogenic variants (36 from our series and 37 published individuals in nine reports) showed developmental delay in all with severe to profound intellectual disability in 67% (n = 41/61) and autistic features in 56% (n = 32/57). Long‐term outcome in 22 individuals older than 12 years (14 in our series and eight published individuals) showed poor cognitive, psychiatric, and behavioral outcome. Epilepsy course was variable. Missense variants were associated with more frequent and more severe epilepsy compared to truncating variants. Significance: Our study describes the phenotypic spectrum of KCNB1 encephalopathy, which varies from severe DEE to DE with or without epilepsy. Although cognitive impairment is worse in patients with DEE, long‐term outcome is poor for most and missense variants are associated with more severe epilepsy outcome. Further understanding of disease mechanisms should facilitate the development of targeted therapies, much needed to improve the neurodevelopmental prognosis.